Lying about sexual assault: a qualitative study of detective perspectives on false reporting - Dewald, Stacy (Policing and society, 2022)
Sexual assault is a highly underreported crime, with only about one-third of victims reporting to the police. There are several reasons why victims are reluctant to report to the police, including fear of not being believed. While research estimates that only 2–8% of sexual assault reports/allegations are false, police officers have been shown to believe that false reporting occurs more frequently than it actually does, which can influence how the case progresses through the legal system. However, little research has explored how detectives come to determine that a report is ‘false’ through individual and structural influences, and how they respond to the constructed lying victim following this determination. The present study uses participant observation and qualitative interviews with detectives in a U.S. suburban police department to examine the institutional frames used when detectives construct sexual assault victims and determine if a case is false. The data indicate that determining if a victim is giving a false report is a complicated process that appears to be influenced by the institutional frames of the department and the individual-level attitudes of the detective including adherence to rape myths. We make recommendations for policing practices to increase the strength of investigations via victim cooperation and provide ideas for further research to build on this study.